Effectiveness of the Cepet Mule Program in Administrative Services: Efektivitas Program Cepet Mule Dalam Pelayanan Administrasi - Nazalia, Desy; Riyadh UB, Ahmad (Universitas Muhammadiyah Sidoarjo, 2022)
The Cepet Mule program is one of the public service innovations in the Tulangan District, Sidoarjo Regency based on an online system that aims to facilitate the community in the process of managing population administration documents to be more effective and efficient. As long as the Cepet Mule program is running, there are still some obstacles in its implementation. This study aims to analyze and describe the effectiveness of the Cepet Mule program in administrative services at the Tulangan District office, Sidoarjo Regency and to find out the supporting factors and inhibiting factors for the effectiveness of the Cepet Mule program in administrative services at the Tulangan District office, Sidoarjo Regency. The research method used is descriptive qualitative, data collection through observation, interviews, documentation. The technique of determining the informants used purposive sampling technique. The results show that the effectiveness of the Cepet Mule program in administrative services at the Tulangan District office, Sidoarjo Regency regarding the accuracy of the program targets has been fairly targeted, but regarding the socialization of the Cepet Mule program it has not been carried out thoroughly, and the achievement of program objectives has not been carried out optimally, and monitoring of its implementation still not optimal. There are several factors that support the Cepet Mule program, namely the existence of regulations from the government, adequate resources, the system can be accessed anywhere, enthusiastic support from the community, and good coordination. While the inhibiting factors for the Cepet Mule program are the difficulty of accessing web pages, the internet network is less stable, the lack of socialization, the public is not familiar with the online service system, and the emergence of new public service system innovations from the district government.